Deciphering the Role of Artificial Intelligence in Medical Sciences: An Update - Siddhant Khanna; Merajul Haque Siddiqui; Shalini Bhushan; Rahul Saxena (National Board of Examinations Journal of Medical Sciences)
Background: The utilization of Artificial intelligence (AI) computer systems is widespread globally, and the growing body of data in diverse scientific fields highlights the significance and requirement of computer-aided, advanced AI systems in contemporary educational systems. AI is becoming more and more of a versatile actor in the medical sciences, spanning all specializations and including diagnostics. Pharmaceutical companies, payers, and healthcare providers are already using various forms of AI. It’s related techniques (machine to deep learning) are frequently employed in disease diagnosis, treatment procedure, and in the evaluation of its side effect. AI techniques utilizes various types of medical diagnostics test data in order to disease diagnosis such as MRI, CT scan, MRI and biochemistry lab reports etc. Better patient-physician communication, remote patient treatment, transcribing prescriptions and other medical documents, and ethical dilemmas are all aided by AI. While humans are still faster at some jobs than computers, the accuracy of modern computer algorithms has lately surpassed that of human experts in the medical sciences. There exist speculations suggesting that medical science roles will eventually be supplanted by people. The current article focused on how AI is transforming medical science along with allied health sector and helping to distinguish between hype and truth, as well as how it might be used to resolve ethical dilemmas and intellectual property rights issues.